Men and things. Continuities and changes in the property rights (Argentina, 19th Century) (Quinto Sol, 2013)
Studies about property rights have only recently started to attract the attention of economic historians in Argentina. In this paper, focusing upon normative aspects, it is our purpose to analyze changes and continuities produced within legal conceptions concerning the rights of property, family and heritage rights by the second half of the 19th century. Debates and speeches from politicians, lawyers and owners, will be analyzed, as well as the expression they found in two key words: the Rural Code of the Province of Buenos Aires, from 1865, and the Civil Code from 1869 (promulgated in 1871), which stated – with different shades of meaning- prívate property as absolute, individual and inalienable. The balance between continuity/break up of conceptions and speeches posed from the law field will also allow to analyze its impact and projection over the configuration of the Argentinian society during the 20th century.
Keywords: Property rights; heritage; family; legal history